Social anxiety as a precursor for depression: Influence of interpersonal rejection and attention to emotional stimuli. (May 2019) - Kraines, Morganne A.; White, Evan J.; Grant, DeMond M.; Wells, Tony T.
Highlights: Attention bias (AB) is important in the development of SAD and MDD. Interpersonal rejection (IR) influences SAD and MDD. We examined whether after IR, increased SAD would show depressogenic biases. SAD was associated with increased AB for sad faces after IR. IR may be a mechanism by which SAD confers risk for MDD via AB. Abstract: Social anxiety disorder (SAD) and major depressive disorder (MDD) are comorbid conditions, and SAD confers risk for MDD. Biased attention and interpersonal rejection are important for the development of SAD and MDD, but little research has examined how these processes may lead to MDD. We hypothesized that interpersonal rejection would result in SAD symptoms being associated with more "depression-like" attention biases. Participants ( n  = 164) completed a measure of SAD symptoms and an eye tracking task before and after a task in which they were randomized to be socially included or rejected. SAD symptoms, inclusion or rejection condition, and the interaction term were entered into separate hierarchical linear regressions predicting change in attention for five emotional faces. Rejection condition significantly moderated the effects of SAD on change in attention to sad, happy, and neutral faces. SAD predicted increased attention to sad faces and decreased attention to happy faces in the rejection condition, but not in the inclusion condition. SAD predicted increased attention to neutral faces in the inclusion condition, but not in the rejection condition. There were no significant effects for angry or disgust. Results suggest that SAD symptoms are associated with more depression-like attention biases in the context of interpersonal rejection.